Intolerance of uncertainty as a mediator of reductions in worry in a cognitive behavioral treatment program for generalized anxiety disorder - Bomyea, J. (J Anxiety Disord, 2015)
Growing evidence suggests that intolerance of uncertainty (IU) is a cognitive vulnerability that is a central feature across diverse anxiety disorders, including generalized anxiety disorder (GAD). Although cognitive behavioral therapy (CBT) has been shown to reduce IU, it remains to be established whether or not reductions in IU mediate reductions in worry. This study examined the process of change in IU and worry in a sample of 28 individuals with GAD who completed CBT. Changes in IU and worry, assessed bi-weekly during treatment, were analyzed using multilevel mediation models. Results revealed that change in IU mediated change in worry (ab = -0.20; 95% CI [-.35, -.09]), but change in worry did not mediate change in IU (ab = -0.16; 95% CI [-.06, .12]). Findings indicated that reductions in IU accounted for 59% of the reductions in worry observed over the course of treatment, suggesting that changes in IU are not simply concomitants of changes in worry. Findings support the idea that IU is a critical construct underlying GAD.